High density of CD8 T cell and immune imbalance of T lymphocytes subsets are associated with proliferative verrucous leukoplakia. Issue 1 (3rd September 2022) - Fernandes, Darcy; Barbeiro, Camila de Oliveira; Palaçon, Mariana Paravani; Biancardi, Mariel Ruivo; Ferrisse, Túlio Morandin; Silveira, Heitor Albergoni; Castilho, Rogerio Moraes; de Almeida, Luciana Yamamoto; Leon, Jorge Esquiche; Bufalino, Andreia
Abstract: Oral leukoplakia (OL) and proliferative verrucous leukoplakia (PVL) are oral potentially malignant disorders (OPMDs) that microscopically show no or varying degrees of dysplasia. Even sharing clinical and microscopic aspects, PVL shows a more aggressive clinical behaviour, with a malignant transformation rate greater than 40%. Inflammatory infiltrate associated with dysplastic lesions may favour malignant transformation of OPMDs. This study aimed to evaluate the density of T cells and cytokines in dysplastic lesions from OL and PVL patients. Additionally, we evaluated whether soluble products produced in vitro by dysplastic keratinocytes are capable of modulating apoptosis rates and Th phenotype (Th1, Th2, Th17 and Treg) of peripheral blood mononuclear cells. The density of CD3, CD4 and CD8 T cells was assessed by immunohistochemistry. Cytokines and chemokines profile from frozen tissue samples were analysed using the LUMINEX system. Apoptosis rates and Th phenotype modulation were evaluated by flow cytometry. Our results showed an increase in the number of CD8 T cell in the subepithelial region from PVL dysplastic lesions in relation to OL samples. PVL showed increased levels of IL‐5 and a decrease in IL‐1β and IFN‐γ levels compared to OL. Soluble products of PVL and oral carcinoma cell cultures were able to reduce apoptosis rate and promote an imbalance of Th1/Th2 and Th17/Treg. The high‐subepithelial density of CD8 T cells and immune imbalance of T lymphocytes subsets probably play an important role in the pathogenesis of PVL and may explain its more aggressive behaviour in relation to OL. Abstract : Inflammatory infiltrate associated with dysplastic lesions may favour malignant transformation of oral potentially malignant disorders. This study shows that dysplastic lesions of patients with proliferative verrucous leukoplakia (PVL) have a high density of subepithelial CD8 T cells in relation to dysplastic lesions of oral leukoplakia. Additionally, the correlation between cytokine/chemokine levels and immunohistochemical staining for CD8 T cells in dysplastic PVL lesions, suggests that the immune exhaustion phenomenon of CD8 T cells may be related to the high malignant rates observed in PVL patients.